Group Art Therapy for the Psychosocial Dimension of Epilepsy: A Perspective and a Preliminary Mixed-Methods Study - Smallwood, Ellen; Legari, Stephen; Sheldon, Signy (Canadian Journal of Counselling and Psychotherapy, 2020)
This article consists of a preliminary study that chronicles an 8-week group art therapy program for people with epilepsy, located in a fine-art museum setting. The study is situated in theories of psychosocial stigma. The primary purpose was to explore whether art therapy could be an effective method to address the psychosocial component of epilepsy treatment in Canada. Secondary questions explored the roles of an open-studio approach and an art therapy program delivered in a fine-art museum context. A mixed-methods (convergent, parallel) design examined the program’s impact for six adults between the ages of 18 and 45 with epilepsy. Psychosocial questionnaires and interviews were administered before and after the group program, and session artworks were examined with Appleton’s (2001) art therapy trauma paradigm. Two groups were compared based on attendance (i.e., attend versus no-attend). Participants who had attended group sessions had substantially reduced scores on questionnaires assessing stress and depression and increased scores on questionnaires assessing self-esteem and quality of life compared to participants who did not attend. The interviews revealed that art therapy increased the attend group’s ability to talk about the impact of epilepsy, to express grief, to make social connections, to navigate treatment stress, and to foster emotional regulation. Group art therapy may improve the psychosocial treatment dimension of epilepsy while acknowledging systemic stigma and social barriers.